Learning to Live Through Loss: Understanding Men Who Grieve - Carolyn S. Wilken (EDIS)
FCS-2266, a 4-page fact sheet by Carolyn Wilken, is one in a series of six publications dealing with grief, death, and loss. This document explores the ways that men grieve and offers suggestions for helping and supporting the grieving widower or father. Published by the UF Department of Family, Youth and Community Sciences, November 2006.